2023
DOI: 10.1101/2023.05.11.540322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A ubiquitous GC content signature underlies multimodal mRNA regulation by DDX3X

Abstract: The road from transcription to protein synthesis is paved with many obstacles, allowing for several modes of post-transcriptional regulation of gene expression. A fundamental player in mRNA biology is DDX3X, an RNA binding protein that canonically regulates mRNA translation. By monitoring dynamics of mRNA abundance and translation following DDX3X depletion, we observe stabilization of translationally suppressed mRNAs. We use interpretable statistical learning models to uncover GC content in the coding sequence… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…When synonymous human codons are compared, common codons tend to be GC-rich, and thus may be associated with higher rates of translation elongation [ 111 ]. GC-rich ORFs also protect mRNAs against cytoplasmic decay [ 53 , 111 , 112 ]. Despite all these findings, it has been found that selection between codons for translation optimality in humans is weak and the codon distribution in human protein-coding genes is mostly mediated by non-adaptive evolutionary processes, such as GC-biased gene conversion, which elevates local GC-content [ 113 ].…”
Section: Gc-content: a Second Mrna Identity Feature That Promotes Nuc...mentioning
confidence: 99%
“…When synonymous human codons are compared, common codons tend to be GC-rich, and thus may be associated with higher rates of translation elongation [ 111 ]. GC-rich ORFs also protect mRNAs against cytoplasmic decay [ 53 , 111 , 112 ]. Despite all these findings, it has been found that selection between codons for translation optimality in humans is weak and the codon distribution in human protein-coding genes is mostly mediated by non-adaptive evolutionary processes, such as GC-biased gene conversion, which elevates local GC-content [ 113 ].…”
Section: Gc-content: a Second Mrna Identity Feature That Promotes Nuc...mentioning
confidence: 99%